Comparative Effectiveness of Oral Ivermectin, 1% Permethrin Shampoo, and 4% Dimethicone Liquid Gel in Treatment of Pediculosis Capitis among School Children in Chachoengsao Province, Thailand - Arisa Vannaratha; Supanut Buakaew; Nitkamol Santiwananont; Thidaporn Srisub; Arthitaya Sutthithum; Sudarat Reugjui; Patanin Julsurang; Hatthakorn Lueang-urai; Wirakarn Liamsakul; Rungtawan Boonsombat; Patanawadee Luenpan; Supasek Thangto; et al. (The American Journal of Tropical Medicine and Hygiene, 2026)
ABSTRACT. Pediculosis capitis remains a persistent public health issue, especially in developing countries where resistance to standard neurotoxic pediculicides like permethrin is increasingly prevalent. This study aimed to compare the effectiveness of alternative treatment options against the standard care in a resource-limited setting. We conducted a single-blind randomized controlled trial involving three primary schools in Chachoengsao Province, Thailand (ClinicalTrials.gov: NCT06332872). Eighty-five female participants ages 6–13 years with active infestations were enrolled. Schools were randomly assigned to three treatment arms: 1) oral ivermectin (200 µ g/kg) on Days 0 and 7; 2) 1% permethrin shampoo on Days 0 and 7, or 3) 4% dimethicone liquid gel as a single dose on Day 0. The primary outcome was the cure rate, defined as the absence of live lice and viable nits upon clinical assessment on Day 9. Of the 66 participants included in the final per-protocol analysis, oral ivermectin achieved a cure rate of 95.5% (21/22), which was significantly higher than that of the 1% permethrin standard of care (37.0%; 10/27) and the 4% dimethicone physical suffocant (29.4%; 5/17) ( P